Bridging The Gap: Tackling Students Challenges in Applying Politeness Strategy in English Daily Conversation - Wijayanti, Tri Dwi; Sukmaningrum, Rahmawati; Susanto, Dias Andris (ETERNAL (English Teaching Journal), 2025)
The study examines the difficulties BBC Tlogosari English Course students face when using politeness strategies in daily conversation. Communication is crucial in today's interconnected world, especially for EFL students. The qualitative research study used document analysis and questionnaires to gather information and questions from other students to analyze their experiences. According to the data, students have many challenges that make it hard for them to be polite. Language barriers, especially English, and emotional and cultural issues are among these challenges. The study showed that students used negative politeness strategies to avoid overgeneralization and cultural misunderstandings. These studies emphasize the need for differentiated instructional approaches that address these concerns, adding to current knowledge. This study shows that English politeness education can improve esteem escalation communication and culture. In the long term, this will improve student communication and cultural awareness. This research emphasizes the importance of politeness strategies and EFL contexts and representatives for more research into effective teaching practices that can improve learners. Communicating in English. Thus, by addressing these issues, teachers improve communication skills to the extent that they have cultural competence.